Philosophical perspectives on art - Davies, Stephen, 1950- (Oxford : Oxford University, 2010)
'Philosophical Perspectives on Art' presents a series of essays devoted to two of the most fundamental topics in the philosophy of art: the distinctive character of artworks and what is involved in understanding them as art.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Art -- Philosophy